High-Serum Angiopoietin-Like Protein 3 Levels Associated with Cardiovascular Outcome in Patients with Coronary Artery Disease - Ming-Chun Chen; Bang-Gee Hsu; Chung-Jen Lee; Ji-Hung Wang (International Journal of Hypertension)
Background. Angiopoietin-like protein 3 (ANGPTL3) plays a pivotal role in lipid metabolism and angiogenesis, and there is growing interest regarding the association between ANGPTL3 and coronary artery disease (CAD). This study aims to investigate whether ANGPTL3 levels can be used to predict the future occurrence of major adverse cardiovascular events (MACEs) in patients with CAD. Methods. Overall, 90 patients with CAD were enrolled between January and December 2012. The study’s primary endpoint was incidence of MACEs. Patient follow-up was completed on June 30, 2017. Results. Following a median follow-up period of 54 months, 33 MACEs had occurred. Patients reporting MACEs had lower statin use (P=0.022) and higher serum C-reactive protein (P<0.001) and serum ANGPTL3 (P<0.001) levels than those without MACEs. Kaplan–Meier analysis revealed higher cumulative incidence of CV events in the high ANGPTL3 group (median ANGPTL3 level ≥ 222.37 ng/mL) than in the low ANGPTL3 group (log-rank P=0.046). Multivariable Cox regression analysis demonstrated that ANGPTL3 levels were independently associated with MACEs in patients with CAD (hazard ratio: 1.003; 95% confidence interval: 1.000–1.005; P=0.026) after adjusted for age, gender, and body mass index, classical risk factors, and potential confounders. Conclusions. Serum ANGPTL3 levels could serve as a biomarker for future occurrence of MACEs in patients with CAD.